KAJIAN SIFAT FISIKO-KIMIA TEPUNG AMPAS TAHU DITINJAU DARI LAMA PERENDAMAN DALAM NATRIUM METABISULFIT (Na2S2O5) DAN LAMA PENGERINGAN - Rahot Manto Sinaga; Netti Herawati; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The purpose of this research is to obtain the best combination of treatments between the soaking time of sodium metabisulfite (Na2S2O5) and the drying time of the physico-chemical of tofu pulp flour. This research was conducted with nine treatment combinations and three replications. The treatment used was soaking time (L) and drying time (P). L1P1 (15 minutes, 3 hours), L1P2 (15 minutes, 4 hours), L1P3 (15 soaking, 5 hours), L2P1 (30 minutes, 3 hours), L2P2 (30 minutes, 4 hours), L2P3 (30 minutes, 5 hours), L3P1 (45 minutes, 3 hours), L3P2 (45 minutes, 4 hours), L3P3 (45 minutes, 5 hour). The treatments of selected in this research was L3P1 with  water content of 6.47 %, ash content of 1.92 %, protein content of 17.03 %, and sensory assessment produced a rather white color with a score of 3.77, the aroma was rather unpleasant with a score of 3.07, and a rather subtle texture with a score of 3.60.